HANSENÍASE NA POPULAÇÃO ESCOLAR DE UM MUNICÍPIO HIPERENDÊMICO DO MARANHÃO - Lima, Themys Danyelle Val (2015)
Leprosy is a disease caused by Mycobacterium leprae, or Hansen bacillus, obligate intracellular parasite, affinity with skin cells and cells of the peripheral nerves, which settles in the body of the infected person and can multiply. The involvement of the disease in children under 15 is a priority of the National Program of Leprosy Control (PNCH) of the Department of Epidemiological Surveillance of the Ministry of Health, for when the disease manifests in childhood indicates high endemicity. This is a retrospective cross-sectional study with a quantitative approach in order to investigate the leprosy in rural schoolchildren in the city of Itapecuru-Mirim / MA and characterize the reported cases of leprosy in children under 15 years from 2009 to 2013. In the retrospective study enrolled 36 cases in 2009 to 2013 and found most frequent in females (72.3%), the age group 06-10 years (52.7%) 83.3% had less than 05 lesions; tuberculoid clinical form (58.3%); paucibacillary classification (66.6%), lack of nerves affected (94.4%); smear microscopy was not performed in 83.3% of cases; diagnostic spontaneous demand (47.2%); Disability zero degree (91.6%). In the examination of household contacts, the year 2013 had 100% of the contacts examined. For cross-sectional study was conducted active case finding in the school population and obtained higher frequency in females (75%); corresponding to 11 years old (50%); own home (50%); more than a minimum wage that income (50%); tuberculoid clinical form (50%); physical disability and no damage to the nerves (75%); likely ignored source of contagion (50%); presence of a BCG scar (75%); Previous treatment for these symptoms (75%); identified previous problem were dermatophytosis (75%). The study allowed the identification of 04 cases of leprosy in children under 15 years, highlighting the importance of further studies in this population.